Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/ijch.201700056
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Hydrofunctionalizations and Spiroketalizations of Alkynes as Key Steps in Total Synthesis

Abstract: This contribution summarizes the application of homogeneous gold catalysis in hydrofunctionalization and spiroketalization reactions in total synthesis, the most frequent applications of gold catalysis in that sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 139 publications
0
14
0
Order By: Relevance
“…We recognized an opportunity to craft this substructure, which features a double anomeric effect, via π-acid catalysis. 12 , 13 This allows the masked C18-carbonyl group to be encoded as a triple bond, which, in turn, should facilitate the build-up of the carbon skeleton from smaller subunits. The homoallylic alcohol at C27 was deemed another privileged assembly point, given the huge repertoire of known asymmetric allylation reactions.…”
mentioning
confidence: 99%
“…We recognized an opportunity to craft this substructure, which features a double anomeric effect, via π-acid catalysis. 12 , 13 This allows the masked C18-carbonyl group to be encoded as a triple bond, which, in turn, should facilitate the build-up of the carbon skeleton from smaller subunits. The homoallylic alcohol at C27 was deemed another privileged assembly point, given the huge repertoire of known asymmetric allylation reactions.…”
mentioning
confidence: 99%
“…Capitalizing on the unique soft π-acidic nature of gold complexes, [20][21][22] a number of transformations ranging from mono- [23][24][25][26][27] and difunctionalization [28] of CÀ C bonds, enyne cycloisomerization, [29][30][31][32][33][34] diyne cycloisomerization, [35,36] carbene transfer reactions, [37][38][39][40][41][42] etc. have been developed, which are now being routinely executed in the synthesis of simple to complex natural products [43][44][45][46][47] as well as various materials. [48] Yet, accessing efficient methodologies based on gold-catalyzed CÀ H functionalization is still underdeveloped.…”
Section: Introduction 1gold-catalyzed Cà H Functionalization Reactionsmentioning
confidence: 99%
“…In 1987, the first homogeneous gold-catalyzed addition of nucleophiles to alkynes was realized by the group of Utimoto using sodium tetrachloroaurate dihydrate. , One decade later, Teles et al and Tanaka et al demonstrated the possibility of activating alkynes using gold­(I) complexes. From that point, the field of gold­(I) catalysis started to gain momentum year after year and still today remains one of the most active areas of research in organometallic chemistry. , This comes as a consequence of the ability of gold­(I) complexes to activate π bonds in a very selective manner. Its potential, attributed partially to relativistic effects, is illustrated by the wide molecular complexity that can be built through the gold­(I)-catalyzed cycloisomerization of enynes (Scheme ). …”
Section: Introductionmentioning
confidence: 99%